Correction to: Fungal succession, litter decomposition and root nitrogen supply in a tropical oil palm plantation - Aisjah R. Ryadin; Nur Edy; Upik Yelianti; Rodica Pena; Andrea Polle (Plant and Soil, 2026)

Fungal succession, litter decomposition and root nitrogen supply in a tropical oil palm plantation - Aisjah R. Ryadin; Nur Edy; Upik Yelianti; Rodica Pena; Andrea Polle (Plant and Soil, 2025)
Background and Aims Industrial oil palm plantation management degrades tropical soils and disrupts ecosystem functions. Applying oil palm leaf litter can help restore soil fertility, but the underlying fungal-driven decomposition and nitrogen recycling remain understudied. This study examines fungal succession in degrading oil palm leaf litter, the fate of litter-derived nitrogen in soil and roots, and the potential for the restoration of fungal biodiversity. Methods We produced 15 N-labelled oil palms and exposed dry leaf litter in 2-mm and 37-µm mesh bags within a plantation. The finer mesh allowed microbial access but restricted roots and most detritivores. We measured litter mass loss, carbon and nitrogen dynamics, and fungal communities via ITS barcoding over six months. Root ingrowth and soil chemistry were also analyzed. Results Litter mass decreased by 70% in both mesh types, with soil accumulating litter-derived 15 N. Fine roots grew into the mesh after three months and took up 15 N , demonstrating nitrogen recycling. Fungal succession displayed clear temporal patterns: early colonizers thrived with higher C/N ratios (Hypocreales, Pleosporales, Chaetothyriales), while late colonizers (e.g., Sordariales, Pleosporales, Chaetosphaeriales ) correlated with C degradation. Arbuscular mycorrhizal fungi increased with declining C/N ratios and coincided with root growth. Conclusions Oil palm litter enhances nitrogen availability, fosters AMF diversity , and improves degraded soils. The numerous uncharacterized fungi in litter decomposition highlight the need for further research into their functional roles for sustainable soil restoration.

Drought, forest management, and soil chemistry affect fine root biomass and nutrient contents in 150 temperate forests plots - Yang Yang; Johannes Ballauff; Andrea Polle (Forest Ecology and Management, 2025)

Effects of cover crops and microbial inoculants in different farming systems on soil microbial communities and yield of maize - Soheila Lahijanian; Jacob Schmidt; Ulf Feuerstein; Andrea Polle (Biology and Fertility of Soils, 2025)
We studied the effects of cover crop treatments (fallow or cover crop) and microbial grain inoculation (control, arbuscular mycorrhizal fungi (AMF), and AMF + bacteria) on soil microbial diversity, community composition, and maize yield across four field sites characterized by different farming systems over two consecutive years. Farming system emerged as the dominant factor driving variations in microbial community composition and diversity. The highest AMF and bacterial diversities were observed in the organic system, while the conventional systems exhibited the lowest diversity. Soil properties and management influenced the microbial community in each field site, whereas weather conditions were less important, due to the proximity of the field locations. Microbial grain inoculation significantly increased maize yield in the high-fertility conventional field, while cover cropping improved yield in the organic and transitional fields. Our study demonstrates that the effects of microbial inoculation and cover cropping are profoundly context-dependent, highlighting the complex interplay between these treatments and field site characteristics, and agricultural management practices. By identifying the specific contexts in which inoculation and cover cropping yield tangible benefits, our study promotes a more targeted, systems-based approach to sustainable agricultural intensification.

Organic substrate quality influences microbial community assembly and nitrogen transport to plants in the hyphosphere of a temperate grassland soil - Luise Brandt; Anna Abrahão; Sven Marhan; Johannes Ballauff; Heike Haslwimmer; Andrea Polle; Ellen Kandeler (Soil Biology and Biochemistry, 2025)

Mycorrhization, root tip vitality and biomass of Fagus sylvatica, Picea abies and Pseudotsuga menziesii in monospecific and mixed combinations under water reduction and nitrogen addition - Michela Audisio; Holger Sennhenn-Reulen; Ilka Schott; Sharath Shyamappa Paligi; Klara Mrak; Dietrich Hertel; Christoph Leuschner; Andrea Polle (Trees, 2024)
Key message In mixed combinations, the negative impact of water reduction and N addition is mitigated for F. sylvatica , but not for conifers. Insight into the responses of trees in mixed and monospecific cultivation to water scarcity and nitrogen (N) excess is necessary to recommend suitable tree mixtures for future European forests. Our aim was to investigate the impact of water reduction, N addition or water reduction + N addition in comparison with control (well-watered, no excess N) on mycorrhizal roots and biomass of three temperate forest species ( Fagus sylvatica Fs, Picea abies Pa, and Pseudotsuga menziesii Pm) grown in monospecific (FsFs, PaPa, PmPm) and mixed combinations (PaFs, PmFs). We predicted the probability of the responses with a Bayesian approach. Mycorrhizal colonization declined marginally for P. menziesii in PmFs under water reduction. Under water reduction and N addition combined, we found a decline in root tip vitality of F. sylvatica in PaFs and of P. abies in PaPa. F. sylvatica shoot biomass declined under water reduction + N addition in the monospecific combination. P. abies and P. menziesii had lower root biomass in mixture with F. sylvatica under water reduction + N addition and under water reduction as single factor, respectively. With water reduction and N addition, P. menziesii performed better than P. abies in terms of biomass production. F. sylvatica had a growth advantage in mixture with conifers instead of conspecifics. These findings suggest that young trees show rapid and interspecific responses to species mixing and water + N availability. The selection of suitable tree species should, therefore, consider their interactive responses to changing abiotic factors.

Mineral type versus environmental filters: What shapes the composition and functions of fungal communities in the mineralosphere of forest soils? - Luise Brandt; Christian Poll; Johannes Ballauff; Marion Schrumpf; De Shorn Bramble; Ingo Schöning; Susanne Ulrich; Klaus Kaiser; Robert Mikutta; Christian Mikutta; Andrea Polle; Ellen Kandeler (Soil Biology and Biochemistry, 2024)

Mother trees, altruistic fungi, and the perils of plant personification - David G. Robinson; Christian Ammer; Andrea Polle; Jürgen Bauhus; Roni Aloni; Peter Annighöfer; Tobias I. Baskin; Michael R. Blatt; Andreas Bolte; Harald Bugmann; Jerry D. Cohen; Peter J. Davies; et al. (Trends in Plant Science, 2024)

Formation of mineral‐associated organic matter in temperate soils is primarily controlled by mineral type and modified by land use and management intensity - De Shorn E. Bramble; Susanne Ulrich; Ingo Schöning; Robert Mikutta; Luise Brandt; Christian Poll; Ellen Kandeler; Christian Mikutta; Alexander Konrad; Jan Siemens; Yang Yang; Andrea Polle; et al. (Global Change Biology, 2024)
Formation of mineral‐associated organic matter (MAOM) supports the accumulation and stabilization of carbon (C) in soil, and thus, is a key factor in the global C cycle. Little is known about the interplay of mineral type, land use and management intensity in MAOM formation, especially on subdecadal time scales. We exposed mineral containers with goethite or illite, the most abundant iron oxide and phyllosilicate clay in temperate soils, for 5 years in topsoils of 150 forest and 150 grassland sites in three regions across Germany. Results show that irrespective of land use and management intensity, more C accumulated on goethite than illite (on average 0.23 ± 0.10 and 0.06 ± 0.03 mg m −2 mineral surface respectively). Carbon accumulation across regions was consistently higher in coniferous forests than in deciduous forests and grasslands. Structural equation models further showed that thinning and harvesting reduced MAOM formation in forests. Formation of MAOM in grasslands was not affected by grazing. Fertilization had opposite effects on MAOM formation, with the positive effect being mediated by enhanced plant productivity and the negative effect by reduced plant species richness. This highlights the caveat of applying fertilizers as a strategy to increase soil C stocks in temperate grasslands. Overall, we demonstrate that the rate and amount of MAOM formation in soil is primarily driven by mineral type, and can be modulated by land use and management intensity even on subdecadal time scales. Our results suggest that temperate soils dominated by oxides have a higher capacity to accumulate and store C than those dominated by phyllosilicate clays, even under circumneutral pH conditions. Therefore, adopting land use and management practices that increase C inputs into oxide‐rich soils that are under their capacity to store C may offer great potential to enhance near‐term soil C sequestration.

Proteomdynamik im Gefäßsystem von Pflanzen - Karl Henrik Kasper; Andrea Polle (BIOspektrum, 2023)
In higher plants, the xylem, which is crucial for water and nutrient transport, also contains a diverse proteome. The composition of the xylem sap proteome responds dynamically to changes in environmental conditions. Important functions are maintenance of structural integrity and defense against invading pathogens. Knowledge on signals that trigger proteomic changes is scarce. Better understanding of these processes may contribute to improve plant performance in a changing climate.

Soil and root nutrient chemistry structure root‐associated fungal assemblages in temperate forests - Dung Quang Nguyen; Dominik Schneider; Nicole Brinkmann; Bin Song; Dennis Janz; Ingo Schöning; Rolf Daniel; Rodica Pena; Andrea Polle (Environmental Microbiology, 2020)
Summary Root‐associated fungi (RAF) link nutrient fluxes between soil and roots and thus play important roles in ecosystem functioning. To enhance our understanding of the factors that control RAF, we fitted statistical models to explain variation in RAF community structure using data from 150 temperate forest sites covering a broad range of environmental conditions and chemical root traits. We found that variation in RAF communities was related to both root traits (e.g., cations, carbohydrates, NO 3 − ) and soil properties (pH, cations, moisture, C/N). The identified drivers were the combined result of distinct response patterns of fungal taxa (determined at the rank of orders) to biotic and abiotic factors. Our results support that RAF community variation is related to evolutionary adaptedness of fungal lineages and consequently, drivers of RAF communities are context‐dependent.

Leaf litter species identity influences biochemical composition of ectomycorrhizal fungi - Nan Yang; Olaf Butenschoen; Rumana Rana; Lars Köhler; Dietrich Hertel; Christoph Leuschner; Stefan Scheu; Andrea Polle; Rodica Pena (Mycorrhiza, 2019)

Assembly processes of trophic guilds in the root mycobiome of temperate forests - Kristina Schröter; Bernd Wemheuer; Rodica Pena; Ingo Schöning; Martin Ehbrecht; Peter Schall; Christian Ammer; Rolf Daniel; Andrea Polle (Molecular Ecology, 2019)
Root‐associated mycobiomes ( RAM s) link plant and soil ecological processes, thereby supporting ecosystem functions. Understanding the forces that govern the assembly of RAM s is key to sustainable ecosystem management. Here, we dissected RAM s according to functional guilds and combined phylogenetic and multivariate analyses to distinguish and quantify the forces driving RAM assembly processes. Across large biogeographic scales (>1,000 km) in temperate forests (>100 plots), RAM s were taxonomically highly distinct but composed of a stable trophic structure encompassing symbiotrophic, ectomycorrhizal (55%), saprotrophic (7%), endotrophic (3%) and pathotrophic fungi ( RAM s is explained by abiotic factors, forest management intensity, dominant tree family ( Fagaceae , Pinaceae ) and root resource traits. Local RAM assemblies are phylogenetically clustered, indicating stronger habitat filtering on roots in dry, acid soils and in conifer stands than in other forest types. The local assembly of ectomycorrhizal communities is driven by forest management intensity. At larger scales, root resource traits and soil p H shift the assembly process of ectomycorrhizal fungi from deterministic to neutral. Neutral or weak deterministic assembly processes are prevalent in saprotrophic and endophytic guilds. The remarkable consistency of the trophic composition of the RAM s suggests that temperate forests attract fungal assemblages that afford functional resilience under the current range of climatic and edaphic conditions. At local scales, the filtering processes that structure symbiotrophic assemblies can be influenced by forest management and tree selection, but at larger scales, environmental cues and host resource traits are the most prevalent forces.

Specialisation and diversity of multiple trophic groups are promoted by different forest features - Caterina Penone; Eric Allan; Santiago Soliveres; María R Felipe‐Lucia; Martin M Gossner; Sebastian Seibold; Nadja K. Simons; Peter Schall; Fons van der Plas; Peter Manning; Rubén D. Manzanedo; Steffen Boch; et al. (Ecology Letters, 2019)
While forest management strongly influences biodiversity, it remains unclear how the structural and compositional changes caused by management affect different community dimensions (e.g. richness, specialisation, abundance or completeness) and how this differs between taxa. We assessed the effects of nine forest features (representing stand structure, heterogeneity and tree composition) on thirteen above‐ and belowground trophic groups of plants, animals, fungi and bacteria in 150 temperate forest plots differing in their management type. Canopy cover decreased light resources, which increased community specialisation but reduced overall diversity and abundance. Features increasing resource types and diversifying microhabitats (admixing of oaks and conifers) were important and mostly affected richness. Belowground groups responded differently to those aboveground and had weaker responses to most forest features. Our results show that we need to consider forest features rather than broad management types and highlight the importance of considering several groups and community dimensions to better inform conservation.

Impact of ectomycorrhizal community composition and soil treatment on inorganic nitrogen nutrition and performance of beech (Fagus sylvatica L.) provenances - Dung Quang Nguyen; Rodica Pena; Andrea Polle (Trees, 2017)

Intraspecific variations in drought response and fitness traits of beech (Fagus sylvatica L.) seedlings from three provenances differing in annual precipitation - Quynh Ngoc Nguyen; Andrea Polle; Rodica Pena (Trees, 2017)

Phylogenetic and functional traits of ectomycorrhizal assemblages in top soil from different biogeographic regions and forest types - Rodica Pena; Christa Lang; Gertrud Lohaus; Steffen Boch; Peter Schall; Ingo Schöning; Christian Ammer; Markus Fischer; Andrea Polle (Mycorrhiza, 2017)

Acid and calcareous soils affect nitrogen nutrition and organic nitrogen uptake by beech seedlings (Fagus sylvatica L.) under drought, and their ectomycorrhizal community structure - Martin Leberecht; Jing Tu; Andrea Polle (Plant and Soil, 2016)

Carbon and nitrogen fluxes between beech and their ectomycorrhizal assemblage - Kerttu Valtanen; Verena Eissfeller; Friderike Beyer; Dietrich Hertel; Stefan Scheu; Andrea Polle (Mycorrhiza, 2014)

Determinants of A cidobacteria activity inferred from the relative abundances of 16 S rRNA transcripts in G erman grassland and forest soils - Bärbel U. Foesel; Verena Nägele; Astrid Naether; Pia K. Wüst; Jan Weinert; Michael Bonkowski; Gertrud Lohaus; Andrea Polle; Fabian Alt; Yvonne Oelmann; Markus Fischer; Michael W. Friedrich; et al. (Environmental Microbiology, 2014)
Summary 16 S rRNA genes and transcripts of A cidobacteria were investigated in 57 grassland and forest soils of three different geographic regions. A cidobacteria contributed 9–31% of bacterial 16 S rRNA genes whereas the relative abundances of the respective transcripts were 4–16%. The specific cellular 16 S rRNA content (determined as molar ratio of rRNA : rRNA genes) ranged between 3 and 80, indicating a low in situ growth rate. Correlations with flagellate numbers, vascular plant diversity and soil respiration suggest that biotic interactions are important determinants of A cidobacteria 16 S rRNA transcript abundances in soils. While the phylogenetic composition of A cidobacteria differed significantly between grassland and forest soils, high throughput denaturing gradient gel electrophoresis and terminal restriction fragment length polymorphism fingerprinting detected 16 S rRNA transcripts of most phylotypes in situ . Partial least squares regression suggested that chemical soil conditions such as pH , total nitrogen, C : N ratio, ammonia concentrations and total phosphorus affect the composition of this active fraction of A cidobacteria . Transcript abundance for individual A cidobacteria phylotypes was found to correlate with particular physicochemical ( pH , temperature, nitrogen or phosphorus) and, most notably, biological parameters (respiration rates, abundances of ciliates or amoebae, vascular plant diversity), providing culture‐independent evidence for a distinct niche specialization of different A cidobacteria even from the same subdivision.

Changes in carbon, nutrients and stoichiometric relations under different soil depths, plant tissues and ages in black locust plantations - Hong Li; Jing Li; Yalong He; Shaojun Li; Zongsuo Liang; Changhui Peng; Andrea Polle; Zhi-Bin Luo (Acta Physiologiae Plantarum, 2013)

Minor contribution of leaf litter to N nutrition of beech (Fagus sylvatica) seedlings in a mountainous beech forest of Southern Germany - Chanjuan Guo; Judy Simon; Rainer Gasche; Pascale Sarah Naumann; Carolin Bimüller; Rodica Pena; Andrea Polle; Ingrid Kögel-Knabner; Bernd Zeller; Heinz Rennenberg; Michael Dannenmann (Plant and Soil, 2013)

Preferential use of root litter compared to leaf litter by beech seedlings and soil microorganisms - Chanjuan Guo; Michael Dannenmann; Rainer Gasche; Bernd Zeller; Hans Papen; Andrea Polle; Heinz Rennenberg; Judy Simon (Plant and Soil, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Jie Luo; Jingjing Qin; Fangfang He; Hong Li; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Planta, 2013)

Cadmium tolerance in six poplar species - Jiali He; Chaofeng Ma; Yonglu Ma; Hong Li; Jingquan Kang; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Environmental Science and Pollution Research, 2013)

Nitrogen fertilization has differential effects on N allocation and lignin in two Populus species with contrasting ecology - Dejuan Euring; Christian Löfke; Thomas Teichmann; Andrea Polle (Trees, 2012)

Relating genetic variation of ecologically important tree traits to associated organisms in full-sib aspen families - Frauke Kleemann; Maximilian von Fragstein; Barbara Vornam; Annika Müller; Christoph Leuschner; Andrea Holzschuh; Teja Tscharntke; Reiner Finkeldey; Andrea Polle (European Journal of Forest Research, 2011)

Host preferences and differential contributions of deciduous tree species shape mycorrhizal species richness in a mixed Central European forest - Christa Lang; Jasmin Seven; Andrea Polle (Mycorrhiza, 2011)

Leaf litter decomposition in temperate deciduous forest stands with a decreasing fraction of beech (Fagus sylvatica) - Mascha Jacob; Karin Viedenz; Andrea Polle; Frank M. Thomas (Oecologia, 2010)

RNAi-mediated suppression of isoprene emission in poplar transiently impacts phenolic metabolism under high temperature and high light intensities: a transcriptomic and metabolomic analysis - Katja Behnke; Andreas Kaiser; Ina Zimmer; Nicolas Brüggemann; Dennis Janz; Andrea Polle; Rüdiger Hampp; Robert Hänsch; Jennifer Popko; Philippe Schmitt-Kopplin; Barbara Ehlting; Heinz Rennenberg; et al. (Plant Molecular Biology, 2010)

Influence of Environmental Pollution on Leaf Properties of Urban Plane Trees, Platanus orientalis L. - Alireza Pourkhabbaz; Nayerah Rastin; Andrea Olbrich; Rosemarie Langenfeld-Heyser; Andrea Polle (Bulletin of Environmental Contamination and Toxicology, 2010)

Functional anatomy of five endangered tropical timber wood species of the family Dipterocarpaceae - Rumana Rana; Rosemarie Langenfeld-Heyser; Reiner Finkeldey; Andrea Polle (Trees, 2009)

Salt stress affects xylem differentiation of grey poplar (Populus × canescens) - María Escalante-Pérez; Silke Lautner; Uwe Nehls; Anita Selle; Markus Teuber; Jörg-Peter Schnitzler; Thomas Teichmann; Payam Fayyaz; Wolfram Hartung; Andrea Polle; Jörg Fromm; Rainer Hedrich; et al. (Planta, 2009)

Wood composition and energy content in a poplar short rotation plantation on fertilized agricultural land in a future CO 2 atmosphere - ZHI‐BIN LUO; ANDREA POLLE (Global Change Biology, 2009)
To study the influence of elevated CO 2 and nitrogen (N) fertilization on wood properties and energy, Populus × euramericana trees were exposed to ambient CO 2 (about 370 μmol mol −1 CO 2 ) or elevated CO 2 (about 550 μmol mol −1 CO 2 ) using Free Air CO 2 Enrichment (FACE) technology in combination with two N levels. Elevated CO 2 was maintained for 5 years. After three growing seasons, the plantation was coppiced, one half of each experimental plot was fertilized and secondary sprouts were harvested after two growing seasons. Fourier transform infrared (FT‐IR) spectra of wood revealed significant effects of both elevated CO 2 and N fertilization on wood chemistry, in particular, significant increases in lignin and decreases in N content. These results were corroborated by chemical analysis. Neither elevated CO 2 nor N fertilization affected the calorific value of wood, which was 19.3 MJ kg −1 . N fertilization enhanced the energy production per land area by 16–69% because of higher aboveground woody biomass production than on nonfertilized land. Estimates indicate that high yielding poplar short rotation cultivation may significantly contribute as an alternative feedstock for energy production.

Quantitative trait loci affecting stomatal density and growth in a Quercus robur progeny: implications for the adaptation to changing environments - OLIVER GAILING; ROSEMARIE LANGENFELD‐HEYSER; ANDREA POLLE; REINER FINKELDEY (Global Change Biology, 2008)
Stomatal traits are important to cope with changes in levels of atmospheric carbon dioxide (CO 2 ) and with changing availability of water. Thus, they are expected to be involved in the reactions of plants to climate change. They are known to show a plastic physiological response to environmental factors such as elevated CO 2 concentrations, but they are also under genetic control and should undergo evolutionary change if selection differs among environments. Stomatal development is regulated by several environmental and genetic signals suggesting a polygenic inheritance. In the present study, F 1 progeny derived from a cross between Quercus robur and Q. robur subsp. slavonica were used to map QTLs (quantitative trait loci) for stomatal densities and growth parameters under nonwater stress conditions in 2 and 3 consecutive years, respectively. The positions of QTLs for stomatal density and growth coincided on six linkage groups. The QTL allele associated with the higher stomatal density was generally associated with taller plants and size increment indicating pleiotropic gene effects or close linkage. The phenotypic effects of the individual QTLs were mostly moderate in terms of phenotypic variance explained. However, a considerable amount of the genetically determined variation was explained by QTLs for stomatal density (from 63.6% to 94.4%). Especially, the QTL on linkage group 11 had a strong and highly significant effect on stomatal densities and growth parameters in all years suggesting a major QTL on this linkage group. The importance to analyse the genetic variation controlling complex adaptive traits in keystone species as oaks is discussed with regard to a better understanding of the reactions of ecosystems to global change.

The influence of the ectomycorrhizal fungus Rhizopogon subareolatus on growth and nutrient element localisation in two varieties of Douglas fir (Pseudotsuga menziesii var. menziesii and var. glauca) in response to manganese stress - Tanja Dučić; Javier Parladé; Andrea Polle (Mycorrhiza, 2008)

Carbon-based secondary metabolites and internal nitrogen pools in Populus nigra under Free Air CO2 Enrichment (FACE) and nitrogen fertilisation - Zhi-Bin Luo; Carlo Calfapietra; Giuseppe Scarascia-Mugnozza; Marion Liberloo; Andrea Polle (Plant and Soil, 2008)

Leaf photosynthesis, fluorescence response to salinity and the relevance to chloroplast salt compartmentation and anti-oxidative stress in two poplars - Ruigang Wang; Shaoliang Chen; Lin Deng; Eberhard Fritz; Aloys Hüttermann; Andrea Polle (Trees, 2007)

Woody biomass production during the second rotation of a bio‐energy Populus plantation increases in a future high CO 2 world - MARION LIBERLOO; CARLO CALFAPIETRA; MARTIN LUKAC; DOUGLAS GODBOLD; ZHI‐BIN LUO; ANDREA POLLE; MARCEL R. HOOSBEEK; OLEVI KULL; MICHAL MAREK; CHRISTINE RAINES; MAURO RUBINO; GAIL TAYLOR; et al. (Global Change Biology, 2006)
The quickly rising atmospheric carbon dioxide (CO 2 )‐levels, justify the need to explore all carbon (C) sequestration possibilities that might mitigate the current CO 2 increase. Here, we report the likely impact of future increases in atmospheric CO 2 on woody biomass production of three poplar species ( Populus alba L. clone 2AS‐11, Populus nigra L. clone Jean Pourtet and Populus × euramericana clone I‐214). Trees were growing in a high‐density coppice plantation during the second rotation (i.e., regrowth after coppice; 2002–2004; POPFACE/EUROFACE). Six plots were studied, half of which were continuously fumigated with CO 2 (FACE; free air carbon dioxide enrichment of 550 ppm). Half of each plot was fertilized to study the interaction between CO 2 and nutrient fertilization. At the end of the second rotation, selective above‐ and belowground harvests were performed to estimate the productivity of this bio‐energy plantation. Fertilization did not affect growth of the poplar trees, which was likely because of the high rates of fertilization during the previous agricultural land use. In contrast, elevated CO 2 enhanced biomass production by up to 29%, and this stimulation did not differ between above‐ and belowground parts. The increased initial stump size resulting from elevated CO 2 during the first rotation (1999–2001) could not solely explain the observed final biomass increase. The larger leaf area index after canopy closure and the absence of any major photosynthetic acclimation after 6 years of fumigation caused the sustained CO 2 ‐induced biomass increase after coppice. These results suggest that, under future CO 2 concentrations, managed poplar coppice systems may exhibit higher potential for C sequestration and, thus, help mitigate climate change when used as a source of C‐neutral energy.

Mycorrhizal Hyphal Turnover as a Dominant Process for Carbon Input into Soil Organic Matter - Douglas L. Godbold; Marcel R. Hoosbeek; Martin Lukac; M. Francesca Cotrufo; Ivan A. Janssens; Reinhart Ceulemans; Andrea Polle; Eef J. Velthorst; Giuseppe Scarascia-Mugnozza; Paolo De Angelis; Franco Miglietta; Alessandro Peressotti (Plant and Soil, 2006)

Carbon partitioning to mobile and structural fractions in poplar wood under elevated CO 2 (EUROFACE) and N fertilization - ZHI‐BIN LUO; CARLO CALFAPIETRA; MARION LIBERLOO; GIUSEPPE SCARASCIA‐MUGNOZZA; ANDREA POLLE (Global Change Biology, 2006)
To determine whether globally increasing atmospheric carbon dioxide (CO 2 ) concentrations can affect carbon partitioning between nonstructural and structural carbon pools in agroforestry plantations, Populus nigra was grown in ambient air (about 370 μmol mol −1 CO 2 ) and in air with elevated CO 2 concentrations (about 550 μmol mol −1 CO 2 ) using free‐air CO 2 enrichment (FACE) technology. FACE was maintained for 5 years. After three growing seasons, the plantation was coppiced and one half of each experimental plot was fertilized with nitrogen. Carbon concentrations and stocks were measured in secondary sprouts in seasons of active growth and dormancy during 2 years after coppicing. Although FACE, N fertilization and season had significant tissue‐specific effects on carbon partitioning to the fractions of structural carbon, soluble sugars and starch as well as to residual soluble carbon, the overall magnitude of these shifts was small. The major effect of FACE and N fertilization was on cell wall biomass production, resulting in about 30% increased above ground stocks of both mobile and immobile carbon pools compared with fertilized trees under ambient CO 2 . Relative C partitioning between mobile and immobile C pools was not significantly affected by FACE or N fertilization. These data demonstrate high metabolic flexibility of P. nigra to maintain C‐homeostasis under changing environmental conditions and illustrate that nonstructural carbon compounds can be utilized more rapidly for structural growth under elevated atmospheric [CO 2 ] in fertilized agroforestry systems. Thus, structural biomass production on abandoned agricultural land may contribute to achieving the goals of the Kyoto protocol.

Leaf litter production and decomposition in a poplar short‐rotation coppice exposed to free air CO 2 enrichment (POPFACE) - M. Francesca Cotrufo; Paolo De Angelis; Andrea Polle (Global Change Biology, 2005)
The capacity of forest ecosystems to sequester C in the soil relies on the net balance between litter production above, as well as, below ground, and decomposition processes. Nitrogen mineralization and its availability for plant growth and microbial activity often control the speed of both processes. Litter production, decomposition and N mineralization are strongly interdependent. Thus, their responses to global environmental changes (i.e. elevated CO 2 , climate, N deposition, etc.) cannot be fully understood if they are studied in isolation. In the present experiment, we investigated litter fall, litter decomposition and N dynamics in decomposing litter of three Populus spp., in the second and third growing season of a short rotation coppice under FACE. Elevated CO 2 did not affect annual litter production but slightly retarded litter fall in the third growing season. In all species, elevated CO 2 lowered N concentration, resulting in a reduction of N input to the soil via litter fall, but did not affect lignin concentrations. Litter decomposition was studied in bags incubated in situ both in control and FACE plots. Litter lost between 15% and 18% of the original mass during the eight months of field incubation. On average, litter produced under elevated CO 2 attained higher residual mass than control litter. On the other end, when litter was incubated in FACE plots it exhibited higher decay rates. These responses were strongly species‐specific. All litter increased their N content during decomposition, indicating immobilization of N from external sources. Independent of the initial quality, litter incubated on FACE soils immobilized less N, possibly as a result of lower N availability in the soil. Indeed, our results refer to a short‐term decomposition experiment. However, according to a longer‐term model extrapolation of our results, we anticipate that in Mediterranean climate, under elevated atmospheric CO 2 , soil organic C pool of forest ecosystems may initially display faster turnover, but soil N availability will eventually limit the process.

Molecular characterization of PeNhaD1: the first member of the NhaD Na+/H+ antiporter family of plant origin - Eric A. Ottow; Andrea Polle; Mikael Brosché; Jaakko Kangasjärvi; Pavel Dibrov; Christian Zörb; Thomas Teichmann (Plant Molecular Biology, 2005)

Influence of free air CO2 enrichment (EUROFACE) and nitrogen fertilisation on the anatomy of juvenile wood of three poplar species after coppicing - Zhi-Bin Luo; Rosemarie Langenfeld-Heyser; Carlo Calfapietra; Andrea Polle (Trees, 2005)

Comparison of Different Methods for Lignin Determination as a Basis for Calibration of Near-Infrared Reflectance Spectroscopy and Implications of Lignoproteins - Kirsten Brinkmann; Lothar Blaschke; Andrea Polle (Journal of Chemical Ecology, 2002)

Osmotic Stress and Ion-Specific Effects on Xylem Abscisic Acid and the Relevance to Salinity Tolerance in Poplar - Shaoliang Chen; Jinke Li; Tianhua Wang; Shasheng Wang; Andrea Polle; Aloys Hüttermann (Journal of Plant Growth Regulation, 2002)

Resistance against oxidative stress in leaves of young beech trees grown in model ecosystems with different soil qualities, elevated CO2, and lachnid infestation - Andrea Polle; D. Peltzer; P. Schwanz (European Journal of Forest Research, 2001)

Growth and protection against oxidative stress in young clones and mature spruce trees ( Picea abies L.) at high altitudes - Andrea Polle; Lars O. Baumbusch; Christa Oschinski; Monika Eiblmeier; Vivian Kuhlenkamp; Birgit Vollrath; Florian Scholz; Heinz Rennenberg (Oecologia, 1999)